Effects of inorganic and organic acids on urine pH in lactating sows - Robert H Hines; H Coa; D J Lee; C A Maloney; J S Park; Joel M DeRouchey; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1998)
Some swine practitioners are advocating the use of dietary acidifiers to reduce urine pH and, thereby, reduce the incidence of urinary tract infections. In our experiment, sows fed an inorganic (phosphoric) acid had lower urine pH than sows fed diets with organic (fumaric, lactic, formic, propionic, and citric) acids. Indeed, the organic acids at 1.5% and 3.0% of the diet increased blood pH and decreased pC02,indicating that these sows were in a more alkalotic (not acidotic) state.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Sows; Urine pH; Acidification